1979
DOI: 10.1063/1.90772
|View full text |Cite
|
Sign up to set email alerts
|

Nature of the 0.111-eV acceptor level in indium-doped silicon

Abstract: Strong evidence is presented that the X-level defect, which produces a 0.111-eV acceptor level in Si : In, is a substitional In–substitutional C (Ins-Cs) pair. The concentration of this defect follows a mass-action law with the In and C concentrations, the association constant being (1.4±0.3) ×10−19 cm−3 at 650 °C. Reversible changes in the X-level concentration between anneal temperatures of 650 and 850 °C are observed, and a pair binding energy of 0.7±0.1 eV is estimated. The electronic properties and temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

1980
1980
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(8 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…(6) No evidence was found for the presence of the 111 meV level associated with the In-C complex (7) or the supershallow level at 18 meV (8) which has been reported in In ion-implanted Si. (6) No evidence was found for the presence of the 111 meV level associated with the In-C complex (7) or the supershallow level at 18 meV (8) which has been reported in In ion-implanted Si.…”
Section: Introductionmentioning
confidence: 99%
“…(6) No evidence was found for the presence of the 111 meV level associated with the In-C complex (7) or the supershallow level at 18 meV (8) which has been reported in In ion-implanted Si. (6) No evidence was found for the presence of the 111 meV level associated with the In-C complex (7) or the supershallow level at 18 meV (8) which has been reported in In ion-implanted Si.…”
Section: Introductionmentioning
confidence: 99%
“…Circle windows of 3.0 mm diameter centered in the squares were opened in the SiO 2 layer. 12 C ϩ was implanted in wafer II with a dose of 4ϫ10 15 cm Ϫ2 and energy of 50 keV. Subsequently,…”
Section: ͓S0021-8979͑99͒06622-0͔mentioning
confidence: 99%
“…Square Van der Pauw devices 16 of 6 mmϫ6 mm were fabricated on the wafers labeled I and II, using a conventional photolitography technique. The p ϩ ohmic contacts were prepared with B ϩ implantation (2ϫ10 15 cm Ϫ2 , 50 keV͒ followed by drive-in in an oxidizing ambient. Circle windows of 3.0 mm diameter centered in the squares were opened in the SiO 2 layer.…”
Section: ͓S0021-8979͑99͒06622-0͔mentioning
confidence: 99%
“…In previous studies, indium doped silicon is often found to contain a shallower defect (sometimes called the “X‐centre”) at around E V + 0.11 eV . An initial study by Baron et al found this defect to scale with the total indium concentration, and to exist in float‐zone as well as Czochralski silicon thus probably ruling out the involvement of oxygen .…”
Section: Discussionmentioning
confidence: 99%